Can heavy metal pollution defend seed germination against heat stress? Effect of heavy metals (Cu2+, Cd2+ and Hg2+) on maize seed germination under high temperature. (September 2016) - Deng, Benliang; Yang, Kejun; Zhang, Yifei; Li, Zuotong
Abstract: Heavy metal pollution, as well as greenhouse effect, has become a serious threat today. Both heavy metal and heat stresses can arrest seed germination. What response can be expected for seed germination under both stress conditions? Here, the effects of heavy metals (Cu 2+, Cd 2+ and Hg 2+ ) on maize seed germination were investigated at 20 °C and 40 °C. Compared with 20 °C, heat stress induced thermodormancy. However, this thermodormancy could be significantly alleviated by the addition of a low concentration of heavy metals. Heavy metals, as well as heat stress induced H2 O2 accumulation in germinating seeds. Interestingly, this low concentration of heavy metal that promoted seed germination could be partly blocked by DMTU (a specific ROS scavenger), irrespective of temperature. Accordingly, H2 O2 addition reinforced this promoting effect on seed germination, which was induced by a low concentration of heavy metal. Furthermore, we found that the NADPH oxidase derived ROS was required for seed germination promoted by the heavy metals. Subsequently, treatment of seeds with fluridone (a specific inhibitor of ABA) or ABA significantly alleviated or aggravated thermodormancy, respectively. However, this alleviation or aggravation could be partly attenuated by a low concentration of heavy metals. In addition, germination that was inhibited by high concentrations of heavy metals was also partly reversed by fluridone. The obtained results support the idea that heavy metal-mediated ROS and hormone interaction can finally affect the thermodormancy release or not. Graphical abstract: Highlights: Trace amount of Cu 2+, Cd 2+ and Hg 2+ treatment can alleviate seed thermodormancy. NADPH oxidase generated ROS are required for this thermodormancy release. Cu 2+ and Cd 2+ have a greater concentration range than Hg 2+ for the promotion of thermodormancy release. Abstract : Trace amount of heavy metal (Cu 2+, Cd 2+ and Hg 2+ ) addition can promote the thermodormancy release of maize seed under high temperature conditions.